An Effective Architecture for Smart City Using Advanced Protocols of Internet of Things - Dr. Jaiteg Singh Khaira, Inderpreet Kaur, Dr. Kamaljit Singh Saini (International Journal of Advanced Science and Technology, 2019)
Designing an effective architecture for the Internet of Things (IoT) still remains a cumbersome task, as it involves the seamless incorporation of a large number of heterogeneous systems involving computing devices, both mechanical as well as digital ones, equipped with relevant identifiers, to transfer data over a variety of networks, excluding completely the human factor from the entire interaction. The paper being presented here proposes an effective and efficient architecture with the advanced protocols for smart cities that does not get affected by any variation in load conditions which can arise due to addition or decrease in the number of devices. Keywords— Effective Architecture for Smart City, Internet of Things, IoT, Smart City